Influência da mastite subclínica estafilocócica sobre as características físico-químicas e celulares do leite - Nicolau, Edmar Soares; Nader Filho, Antonio [UNESP]; Do Amaral, Luiz Augusto [UNESP]; Rossi Jr., Oswaldo Durival [UNESP] (My University, 1996)
One hundred twenty-six milk samples from 63 apparently healthy cows, but positive in the California Mastitis Test were submitted to determinations of pH, acidity, density, butter-fat, total solids, non-fat solids, cryoscopic point, caseine level, chloride level and polymorphonuclear leukocytes. Forty-one cows were infected by coagulase-positive Staphylococcus and 22 by coagulase-negative Staphylococcus. The results obtained in the milk sample analysis from the healthy quarters and infected by coagulase-positive Staphylococcus showed variations of all constituents investigated. However only the pH values (F=4.17*) and the polymorphonuclear leukocytes (F=11.35**) showed significant differences. On the other hand, between the milk samples from healthy quarters and infected quarters by coagulase-negative Staphylococcus, only the polymorphonuclear leukocytes (F=16.29**) showed significant differences.
Influence of subclinical staphylococci mastitis on physical, chemical and cellular milk characteristics
Keywords: Coagulase-negative Staphylococcus; Coagulase-positive Staphylococcus; Milk; Subclinical mastitis